Editorial Note: On Hope - Suvi Rautio (Suomen Antropologi)
Lately, our daily news is engulfed with billowing clouds of despair as democracy slips away and is replaced with emboldened form of authoritarianism. We live in dark times. Global disasters are multiplying with no end in sight. Powerful institutions get away with hypocrisy unchecked. And, history is being rewritten with a force that disrupts the societal and political imaginaries that hold on to the conviction that peace, profound goodness, and care are possible. As this overwhelming feeling of deep despair occupies our attention and affective state of being, instances of real change and hope unfurling in this moment are easily missed. One such example can be found in Serbia, where students have peacefully and fearlessly risen up, calling for revolutionary change. We on the editorial team of Suomen antropologi stand in solidarity with the students and university personnel in Serbia, who in recent months have taken courageous action. As a scholarly journal, we recognise that the demands of the subordinate cannot be sidelined, marginalised, ignored, or silenced. We hear the voices from the ongoing protests, and they are deafening. This is an historic moment and a much-needed reminder of the spark of hope that this world so desperately needs right now.